Project earth science. Astronomy - Smith, P. Sean. (Arlington, VA : National Science Teachers Association Press, 2001)
Contains resources for lessons that teach middle-level students about astronomy, including concept explanations, activities, reproducible pages, related readings, and illustrations and covering the solar systems, how planets form, stars, and other topics.
Includes bibliographical references (p. 140-146).
Professional
Keywords: Astronomy -- Experiments; Astronomy -- Study and teaching (Secondary); Astronomy -- Experiments; Astronomy -- Study and teaching